Analysis of hospitalization trends for ambulatory care sensitive conditions in Piauí/Brazil, 2009-18. (30th September 2020) - Sousa, R; Silva, F; Silva, R; Santos, R; Mouta, J; Cardoso, T; Cardoso, O
Abstract: Introduction: Hospitalizations for ambulatory care sensitive conditions (ACSC) are hospitalizations that can be potentially preventable through care at the first level of contact for health care. In fact, the actions offered in a timely and effective manner can reduce the risk of unnecessary hospitalizations by preventing diseases, controlling acute episodes and managing chronic diseases. Aim: Analyze the trends in hospitalizations for ACSC in Piauí, Brazil, from 2009 to 2018. Methods: Ecological time-series study based on data from the Hospital Information System (SIH) of the public health system (SUS), which comprised all hospitalizations of residents of Piauí, Brazil, in the period from 2009 to 2018. The explanatory variables were the hospitalizations for ACSC groups. For temporal trend analysis, the Prais-Winsten linear regression model was used in the Stata version 14 program. Results: 567, 577 were recorded as ACSC, representing 35.3% of the total hospitalizations (1, 608, 263). Most hospitalizations for ACSC were caused by infectious gastroenteritis (33.5%). The risk of hospitalization for ACSC decreased 36.8%, showing a significant reduction in the trend of the hospitalization rate (Annual Percent Change - APC: -4.6%; 95%CI: -6.4; -2.8). There was a greater decrease in the risk of hospitalization for asthma (70.3%), hypertension (66.4%) and infectious gastroenteritis (61.8%). However, a significant increase was identified for skin infection (6.1 times) and diseases related to prenatal care and childbirth (3.2 times). Conclusions: The reduction in hospitalizations due to ACSC is a result of the strengthening of Primary Health Care as the Brazilian health system organizer and the implementation of the Mais Médicos Program, which enabled the presence of doctors in family health teams, especially in places that had not previously been attended. It is also necessary to develop new studies to expand the discussions and debates on these findings. Key messages: Hospitalizations reflect the living conditions of individuals, with social changes being perceived by changes in hospitalization patterns over time. The strengthening of primary care policies in Brazil was able to reduce hospitalizations for ACSC and it is necessary to further strengthen these practices to improve people's health care.